Effect of a GRIN2A de novo mutation associated with epilepsy and intellectual disability on NMDA receptor currents and Mg2+ block in cultured primary cortical neurons. (26th February 2015) - Marwick, Katie; Skehel, Paul; Hardingham, Giles; Wyllie, David
Abstract: Background GRIN2A encodes the GluN2A subunit of the NMDA receptor (NMDAR), an ionotropic glutamate receptor that has important roles in synaptogenesis and synaptic plasticity. Some individuals with early onset epilepsies and intellectual disability carry heterozygous missense mutations in this gene, including a de-novo mutation in the receptor pore region (GluN2A N615K ). We hypothesised that this mutation underlies the carrier's brain disorder and sought to explore its functional consequences. Methods: We made two-electrode voltage clamp recordings from Xenopus laevis oocytes expressing GluN1/GluN2A N615K (N615K) NMDARs and compared them with wild-type (WT) NMDARs to assess the mutation's effect on potency of inhibition by Mg 2+ and other channel blockers. We then used whole-cell patch-clamping to evaluate NMDAR-mediated currents in mouse primary cortical pyramidal neurons transfected with either GluN2A WT or GluN2A N651K subunits. Means were compared by use of independent two-tailed t tests. Findings: In oocytes, Mg 2+ (1 mM) block at −60 mV was significantly decreased (N615K [n=13], mean 5% [SE 8] vs WT [n=15], 89 [4]; p<0·0001). Furthermore, in N615K (n=17) and WT (n=17) oocytes, block by 10 μM memantine was also reduced (mean 26% [6] vs 75 [7], p<0·0001) as was block by 100 μM amantadine (18% [4] vs 44 [12], p<0·0001). Block by ketamine (N615K, n=14; WT, n=14) was not significantly affected, whereas block by dextromethorphan was increased (N615K [n=9], 56% [8] vs WT [n=8], 44 [6]; p=0·003). In N615K (n=10) and WT (n=10) neurons we observed a significant decrease in Mg 2+ sensitivity (49% [18] vs 95 [5], p<0·0001) and a significant decrease in current density (42 pA/pF [19] vs 61 [20], p=0·044). Interpretation: This study suggests that the disease-associated mutation GluN2A N615K has substantial effects on NMDAR inhibition by both endogenous and exogenous channel blockers, and on NMDA current density. It is plausible that these changes underlie the carrier's phenotype. Funding: Wellcome Trust via an Edinburgh Clinical Academic Training PhD Fellowship.